The life and achievements of Erwin-Félix Lewy-Bertaut (1913–2003). (14th January 2015) - Férey, Gérard; Hodeau, Jean-Louis
Abstract: Erwin-Félix Lewy-Bertaut was initially a lawyer. He left Germany for France when the Nazis rose to power, having been born into a German Jewish family. He became a French citizen in 1936 and embarked upon a scientific career, first in organic chemistry in Bordeaux. The troubles associated with World War II obliged him to move to Grenoble under the protection of Louis Néel. In addition to his creative activity in the new field of inorganic solid state chemistry, he rapidly became a crystallographer and a physicist of magnetism, noted for his impressive activity in both of these domains. He became a pioneer of neutron diffraction and was pivotal to the creation of the Institut Laue-Langevin. Owing to the impact of his work, he was involved in the key international organizations responsible for shaping crystallography and physics. A member of the French Academy of Sciences, Monsieur Bertaut received many international awards. He was a very kind man of culture.